The Role of the Professional Community in the Development of the Engineering Market in Russia - V. G. Zinov; O. A. Yeremchenko (Ekonomika Nauki)
The barriers to the development of the industrial engineering market as a tool to ensure the full life cycle of high technology products in Russia are considered. The problem is the most difficult to overcome barriers attributed to the vague definition of engineering services and the problem of trust between participants. Proposals were substantiated to clarify the content of engineering activities and intensify the professional community in the direction of creating a self-regulatory organization as a generator of communication and certification activities, as well as creating an updated national register of engineering companies.